Can poor institutions explain Brazil’s economic stagnation? A brief review of policy choices and incentives - Matheus Terentin (Journal of Government and Economics)
This article critically examines Brazil's economic stagnation since the 1980s, contesting the overarching view that attributes underdevelopment primarily to poor institutions. While acknowledging Brazil's impressive growth from 1932 to 1980, driven by an entrepreneurial state, the paper argues that the institutional determinants of growth do not offer a plausible explanation for its slowdown. Instead, it presents an alternative perspective rooted in New Developmentalism and structuralist economics, highlighting the detrimental impact of policy shifts initiated in the 1980s. These include the retreat of the developmental state, a decline in public investment, chronically high interest rates, and a persistently overvalued exchange rate, all of which have hampered Brazil's structural transformation. Knowing who benefits and who loses from these policies provides insight into why policymakers persist on this stagnant path, sacrificing sustained growth for momentary gains. It concludes by asserting that policymakers have conveniently used the discourse of public inefficiency to justify withdrawing the government from its role in development. It advocates for a paradigm shift in policymaking, urging recognition that poor institutions are primarily a consequence, not a cause, of underdevelopment.